Las implicaciones del reanálisis del caso de Anna O. para la psicoterapia, Freud y el psicoanálisis (Revista Puertorriqueña de Psicologia, 2016)
The case of Anna O. has been commented extensively by scholar and historians interested in the history of psychotherapy and psychoanalysis. It is widely acknowledged that this case inspired Freud in his early formulations of a dynamic unconscious and the treatment of hysteria. In fact, in the last two decades a formidable number of scholars have written extensively about this patient and about the manner in which Breuer and Freud presented to the scientific world the clinical evidence. In this article, the author critically reviews a number of recent documents and data that sustain the view that Breuer and Freu distorted in considerable ways the clinical situation of Anna O. and the treatment itself. finally, the author reviews a variety of diagnostic labels that have been suggested to explain the phenomenology of Anna O.